Presentations and Challenges in Tuberculosis of Head and Neck Region - Yashveer, J. K. (Indian J Otolaryngol Head Neck Surg, 2015)
(1) To study the different patterns of presentations of tuberculosis in Head and Neck region. (2) To know the importance and reliability of ESR and Mantoux test as an aid in diagnosis of tuberculosis. This study was conducted at Department of ENT and Head and Neck Surgery, Gandhi Medical College, Bhopal, Madhya Pradesh from January 2014 to June 2015. Patients presenting with lesions in the Head and Neck region suspected of tuberculosis were subjected for cytological and histological investigations. Those cases confirmed to be tuberculosis on the basis of either of these tests were included in the study. Study comprised of 113 proven cases of tuberculosis of Head and Neck region. A female preponderance of 1:1.97 (M:F) ratio was noted. Most commonly involved structure was cervical lymph node (92.92 %) followed by larynx, skin and oral mucosa (1.76 %). It was also noted that Mantoux test was positive in 93.8 % of patients and ESR was >30 mm (first hour) in 95.5 % of patients with tuberculosis. Most common presentation of Tuberculosis in Head and Neck area was cervical lymphadenopathy. In a developing country like India the population is mostly in the lower socioeconomic strata. Access to various modern investigations is limited and diagnosis is challenging. Here ESR and Mantoux test are helpful in purusing the case for further evaluation. Based on these pointers cytologically negative cases can be taken up for biopsy.